Ficção de guerra: maus, de Art Spiegelman - Galdino, Evangley de Queiroz (2012)
This research is the corpus Comics Maus. We propose a reflection on the formation of the Comics, taking into consideration their intersemiosis the intersection of writing, visual and audible and its implications for relations between memory and testimony, fundamental to understanding the narrative proposal. That said, the work study raises questions that lead us to rethink the place of his own HQ, commonly associated only entertainment and mass communication. Our goal is to understand how the fine line between fiction and reality becomes complex for any single seizure in history and therefore the past, both individual and collective, and as a mass medium is capable of driving it. The study of HQ show a distinct moment of "witness history" in post-modernity. In studying this work above, we see that, to the extent that aims to become a reality representable dehumanizing and to some extent almost unspeakable act of narrating is at the same time, a reflection on the possibilities of narrative in "postmodern times ". In the first chapter, we outline the particular character of the work, as a testimony of a survivor of a traumatic event and the intimate relationship between individual memory and the collective as unfolding. In the second chapter, we aimed to establish the relationship between Comic, ethics and politics, aiming to understand how effective engagement of some works that have mainly ideological proposals that meet the social minorities. Therefore, we scoped the recent productions concerning the Jewish question by authors such as Will Eisner and Art Spiegelman. In the third chapter chapter, we aim at one of social-semiotic Comics, analyzing it as a hybrid language in which the sounds, the imagistic and verbal are inextricably interwoven. The understanding of semiosis becomes necessary in so far as signs indicate the grounds for understanding the work itself. This premise leads us to analyze the visual metaphor created by Spiegelman: a game between cats and mice, and also shows how to assess the composition of the actual cover, showing the intrinsic relationship between signs and memory. In the fourth chapter, we will cover the lines of history about the Holocaust, noting how the author appropriates historical facts, creating unique fictional representations about this event. Dialogue between History and Arts is defined as a key point to understand how some of these representations are put to us. Both the survival tactics of the Jewish people, as the strategies of surveillance and control and punishment of Nazi system are presented as representations and that is what we seek to identify.. Therefore, as theoretical and methodological principles, we will use the contributions of Pierce, Santaella, Darnton, Benjamin Berman, Siligmann Deleuze, Le Goff and others.